PENGARUH FAKTOR INTERNAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Utami, Destika Maulana; Sulistyarini, Sulistyarini; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearch aims to understand influence internal factors on student learning outcomes on economic subjects class XI IIS in SMA Negeri 9 Pontianak. The method used in this research is descriptive method percentage with research form used is ex post-facto research. The population in this study were students of class XI IIS which amounted to 120 students, with samples taken in this study amounted to 54 students consisting of students of class XI IIS 1, XI IIS 2, and XI IIS 3. The results showed that there is a positive and significant relationship between the independent variable (X) or internal factors and dependent variable (Y) or student learning outcomes with the value of correlation or relationship (R) is equal to 0.729 strong categories. As for the data analysis techniques obtained equation 17.370 + 0.643X. The result of t test shows that tcount> ttable is (7,674> 2,006). So Ha accepted and Ho rejected. Thus it can be said that there is an influence of internal factors on student learning outcomes on economic subjects class XI IIS in SMA Negeri 9 Pontianak. Result of coefficient of determination (R2) equal to 0,531 which mean contribution percentage of influence equal to 53,1% while the rest 46,9% influenced by other factor not studied in this research like external factor covering: family environment, school environment and society environment. Keywords: Internal Factors, Learning Outcomes, Students